Analisis Proses Bending 2 Pada Pembuatan Produk Joint Brake ROD KTMY Untuk Sepeda Motor Honda - Dimas Azhar Baihaqi; Rizal Hanifi; Aa Santosa (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study dicusses the analysis of the banding process in the manufacture of joint brake rod products based on data in a field. Analysis of the bending process that is carried out is to maximize in reducing the percentage of scrap formed in the blank process. The purpose of the analysis in this comparison process is to understand how the bucket elevator works and find out the number of buckets (bowls) in the bucket elevator needed to transport the product. The research method carried out is through direct observation of the literature studies that have been obtained in the form of books or journals and the internet as references. This calculation is carried out to be used as a benchmark as a comparison material from the calculation results with information data on the number of joint brake rods in the field. This comparison material is based on several basic theories and conclusions obtained from the result of calculations. Therefore, the process that occurs in the press machine, especially in the bending process, there are several this that need to be taken into account to produce a good and optimal product. Some of these include bending styles. From this research, it can be concluded that the amount of force for bending process is 8,640 N. The amount of force required for the pad to hold the material during the bending process is 1,160 N. The total force required for the bending process is 10.8T.